ECQA Governance SPICE assessor skills for evaluating integrated risk management scenarios. Issue 8 (15th July 2015) - Ivanyos, János; Sándor‐Kriszt, Éva; Biró, Miklós; Messnarz, Richard; Colomo‐Palacios, Ricardo
Abstract The term of 'scenario' is used for systematically considering integrated risk management aspects of enterprise governance practices implemented at operational and organizational levels. These considerations are focusing on the customized design and continuous improvement of governance objectives, processes and practices enabling the achievement of the concerning enterprise goals. Professionals having been acquiring and evidencing their Governance SPICE Assessor skills are able to provide unique consulting and assurance services for enterprises in optimizing the effects of uncertainties on governance objectives by assessing and evaluating capability of enterprise governance processes. Copyright © 2015 John Wiley & Sons, Ltd.